Effects of ultrasonic impact treatment on pre-fatigue loaded high-strength steel welded joints. (November 2015) - Zhang, Hai; Wang, Dongpo; Xia, Liqian; Lei, Zhenyu; Li, Yizhe
Abstract: Comparative fatigue tests were conducted on as-welded, weld toe peened specimens before and after fatigue loading. Fracture surface, residual stress, microstructure and hardness were determined. The test results showed that as the pre-fatigue loading period extended, deeper cracks may have initiated and propagated and the fatigue life improvement decreased. The processes of ultrasonic peening on welded joints with existing cracks were modeled by finite element analysis. The numerical results indicated that the mechanism of UIT improving fatigue performance included two factors: compressive residual stress and the change of crack orientation. Both effects reduced as the crack became deeper.